2017
DOI: 10.1097/bco.0000000000000478
|View full text |Cite
|
Sign up to set email alerts
|

Closed reduction with or without adductor tenotomy for developmental dysplasia of the hip presenting at walking age

Abstract: Background:Many children with developmental dislocation of the hip especially in underdeveloped countries reach walking age and still remain undiagnosed, which can be detrimental to their growth and development. Because of the lack medical services often encountered in these regions, it would be attractive to find a cheap and effective treatment. Our work evaluated the results of treatment of these children by closed reduction with or without adductor tenotomy in a prospective study.Methods:We included 20 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
1
11
0
5
Order By: Relevance
“…Terjesen et al [24] reported that the most important independent risk factors for a poor long-term outcome was an age of eighteen months or older at the time of reduction. On the contrary, Barakat et al [25] concluded that CR in children between 19 procedures [26] . Herein, we observed the similar outcomes that patients older than 18.35 months at the age of CR may have poor outcomes when compared with younger patients.…”
Section: Discussionmentioning
confidence: 98%
“…Terjesen et al [24] reported that the most important independent risk factors for a poor long-term outcome was an age of eighteen months or older at the time of reduction. On the contrary, Barakat et al [25] concluded that CR in children between 19 procedures [26] . Herein, we observed the similar outcomes that patients older than 18.35 months at the age of CR may have poor outcomes when compared with younger patients.…”
Section: Discussionmentioning
confidence: 98%
“…Наступним методом лікування є застосування іммобілізації кульшових суглобів у фізіологічно-вигідному положенні у гіпсовій пов'язці [1,4]. Інколи закрите вправлення комбінують із застосуванням артрографії та/або міотомії аддукторів [20]. Успіх закритого вправлення залежить від віку (чим старша дитина, тим більші зміни виникають у кульшовому суглобі та тканинах навколо суглоба) [16].…”
Section: вступunclassified
“…до 2 лет, однако при наличии тяжелой степени болезни (выраженное недоразвитие вертлужной впадины, высокий вывих) допускается хирургическое лечение с 6 мес. [15,16]. Типичным же считается применение хирургического метода у детей от двух лет и старше [15,16].…”
unclassified
“…[15,16]. Типичным же считается применение хирургического метода у детей от двух лет и старше [15,16].…”
unclassified
See 1 more Smart Citation